2015
DOI: 10.1177/0268355515596474
|View full text |Cite
|
Sign up to set email alerts
|

Stenting for chronic obstructive venous disease: A current comprehensive meta-analysis and systematic review

Abstract: Objectives: The aim of this article was to summarize the efficacy and safety of venous stents in chronic obstructive venous disease (COVD) including postthrombotic syndrome (PTS) and nonthrombotic iliac vein lesions (NIVL). Methods: We searched PubMed for case series (prospective and retrospective) that focused on venous stents in the treatment of COVD published between 1st January, 2000 and 15th July, 2014. Then, we analyzed the perioperative complications, subsequent antithrombotic treatment, clinical outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 28 publications
2
37
0
3
Order By: Relevance
“…Patency rates in patients with IVCS were 90%, 100%, and 100% at 60 months and were comparable with previous studies. 2,3,4 The main patency related issues were allied to stent geometry and stent placement problems. Regarding this, future outcomes are expected to improve even more with the introduction of dedicated venous stents, as excellent results of a dedicated venous stent during 12 months follow-up already support this.…”
Section: Discussionmentioning
confidence: 99%
“…Patency rates in patients with IVCS were 90%, 100%, and 100% at 60 months and were comparable with previous studies. 2,3,4 The main patency related issues were allied to stent geometry and stent placement problems. Regarding this, future outcomes are expected to improve even more with the introduction of dedicated venous stents, as excellent results of a dedicated venous stent during 12 months follow-up already support this.…”
Section: Discussionmentioning
confidence: 99%
“…The venous clinical severity score and Villalta score were obtained by the same physician for all patients, as were general patient characteristics, such as duration of complaints and previous medical history. Patients were allocated to one of four groups according to the Villalta scale: no PTS (0-4), mild PTS (5-9), moderate PTS (10)(11)(12)(13)(14) or severe PTS (> 14 or the presence of an ulcer) [2]. This study was approved by the medical ethical review board (METC 13-2-027) and principles according to the 2013-revised declaration of Helsinki were followed.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…However, residual deep venous obstruction appears to have a more prominent effect on PTS, especially when occurring in the iliac veins [8,9]. Although there is evidence that treatment of these types of obstruction by percutaneous transluminal angioplasty and stenting may be effective, little is known about the hemodynamic consequences of deep venous obstructive disease [10][11][12][13][14]. In the past, extensive research involving invasive pressure measurements was performed, with the focus on deep vein incompetence and pressure measurements in the dorsal foot veins [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…More evidences in the literature showed that mild degrees of stenosis could be responsible of venous hypertension and, as a consequence, of chronic venous disease [1,[20][21][22].…”
Section: Discussionmentioning
confidence: 99%